Sub corneal Pustular Dermatosis in a Middle- Aged Woman: A Rare Presentation with Diagnostic Challenges and Successful Topical Corticosteroid Therapy (Sir Salimullah Medical College Journal, 2026)
Sub corneal pustular dermatosis (SPD), also known as Sneddon–Wilkinson disease, is a rare, chronic, relapsing neutrophilic dermatosis characterized by the presence of superficial pustules. It predominantly affects middle-aged to elderly women and commonly presents with flaccid pustules over the trunk and intertriginous areas. Due to its clinical overlap, SPD is often mistaken for other dermatologic conditions such as pustular psoriasis, impetigo, and IgA pemphigus. Immunologic studies separate SPD-type IgA pemphigus from SPD and pustular psoriasis. Dapsone remains the first-line treatment for SPD, although dapsone-resistant cases have been increasingly reported. Other therapies have been used singly or as adjunctive therapy with success, such as corticosteroids, immunosuppressive agents, tumor necrosis factor inhibitors, and ultraviolet light therapy. We present the case of a 48-year-old woman with recurrent annular plaques localized to the right forearm. Histopathologic examination confirmed a diagnosis of SPD. The condition was effectively managed with topical corticosteroids alone. This case underscores the diagnostic challenges associated with SPD and demonstrates the potential effectiveness of topical therapy in mild presentations.Sir Salimullah Med Coll J 2025; 33: 144-149